Allosteric water and phosphate effects in Hoplosternum littorale hemoglobins - Peres, P.; Junior, WFD; Bonilla-Rodriguez, G. O. (Blackwell Publishing, 2004)
This paper reports the results obtained using the osmotic stress method applied to the purified cathodic and anodic hemoglobins (Hbs) from the catfish Hoplosternum littorale, a species that displays facultative accessorial air oxygenation. We demonstrate that water potential affects the oxygen affinity of H. littorale Hbs in the presence of an inert solute (sucrose). Oxygen affinity increases when water activity increases, indicating that water molecules stabilize the high-affinity state of the Hb. This effect is the same as that observed in tetrameric vertebrate Hbs. We show that both anodic and cathodic Hbs show conformational substrates similar to other vertebrate Hbs. For both Hbs, addition of anionic effectors, especially chloride, strongly increases the number of water molecules bound, although anodic Hb did not exhibit sensitivity to saturating levels of ATP. Accordingly, for both Hbs, we propose that the deoxy conformations coexist in at least two anion-dependent allosteric states, T-o and T-x, as occurs for human Hb. We found a single phosphate binding site for the cathodic Hb.
Keywords: hemoglobin; osmotic-stress; catfish